Measuring Coverage in MNCH: Current Indicators for Measuring Coverage of Diarrhea Treatment Interventions and Opportunities for Improvement - Fischer Walker, Christa L.; Fontaine, Olivier; Black, Robert E. (PLoS medicine, 2013)
Diarrhea morbidity and mortality remain important child health problems in low- and middle-income countries. The treatment of diarrhea and accurate measurement of treatment coverage are critical if child mortality is going to continue to decline. In this review, we examine diarrhea treatment coverage indicators collected in two large-scale community-based household surveys--the Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS). Current surveys do not distinguish between children with mild diarrhea episodes and those at risk for dehydration. Additional disease severity questions may improve the identification of cases of severe diarrhea but research is needed to identify indicators with the highest sensitivity and specificity. We also review the current treatment indicators in these surveys and highlight three areas for improvement and research. First, specific questions on fluids other than oral rehydration salts (ORS) should be eliminated to refocus the treatment of dehydration on ORS and to prevent confusion between prevention and treatment of dehydration. Second, consistency across surveys and throughout translations is needed for questions about the caregiver behavior of "offering" the sick child fluid and food. Third, breastfeeding should be separated from other fluid and food questions to capture the frequency and duration of nursing sessions offered during the illness. Research is also needed to assess the accuracy of the current zinc indicator to determine if caregivers are correctly recalling zinc treatment for current and recent diarrhea episodes.